“La participación de los padres de familia en el proceso enseñanza – aprendizaje de los estudiantes de tercero de básica de la Unidad Educativa “Ramón Páez” del cantón Latacunga” - Chanatasig Toapanta, Leidy (2021)
Parents generally, are not usually immersed in the teaching-learning process of their children. In the sixties decade, parents are added in a correct way in educational activity. During COVID-19 pandemic, parents had to adapt in the educational process of their children. The objective proposed in this work is to make a study on the participation of parents in the educational process of students in third level from "Ramón Páez" Elementary School of Patután Parish, Latacunga canton and Cotopaxi province. According to the concepts that were compiled in the Theoretical Framework. It could established that in the teaching-learning process of the students, several people has participated, such as the teacher and student and also parents and authorities. The participation of the father is essential to ensure a good development of the system. However, during the health emergency, parents took a leading and decisive role in this labor. For the determination of the participation of the parents in the teaching-learning process of the students, who are the principal objective of this study, the qualitative methodology was applied with a descriptive focus and the tool applied was the interview. It was possible the collection of all the information about the experience that the parents had in the teaching-learning process of their kids. These interviews were used to make some stories, which were encoded in the book form and after will be launched in social networks. In pandemic context the results shows that the inclusion of the parents in the teaching-learning process in students of third level in “Ramón Páez” elementary school was effectively. The recommendation is the wide diffusion of this work for helping as the base for similar studies